2021
DOI: 10.3390/su132111896
|View full text |Cite
|
Sign up to set email alerts
|

Paper Sensors Based on Fluorescence Changes of Carbon Nanodots for Optical Detection of Nanomaterials

Abstract: A paper sensor was designed in order to detect the presence of nanomaterials, such as ZnO and silica nanoparticles, as well as graphene nanoplatelets (GnP), based on fluorescence changes of carbon nanodots. Paper strips were functionalized with carbon nanodots using polyvinyl alcohol (PVA) as binder. The carbon nanodots were highly fluorescent and, hence, rendered the (cellulosic) paper stripes emissive. In the presence of silica and ZnO nanoparticles, the fluorescence emission of the carbon nanodots was quenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The addition of the dots did not significantly affect the emission color of the ZnO part. It has been previously demonstrated that the presence of ZnO quenches the emission of the carbon quantum dots due to electron-hole recombination caused by non-radiative electron transfer between the materials [39][40][41]. On the other hand it turned the porous Si part from red to purple, as expected.…”
Section: Resultssupporting
confidence: 60%
“…The addition of the dots did not significantly affect the emission color of the ZnO part. It has been previously demonstrated that the presence of ZnO quenches the emission of the carbon quantum dots due to electron-hole recombination caused by non-radiative electron transfer between the materials [39][40][41]. On the other hand it turned the porous Si part from red to purple, as expected.…”
Section: Resultssupporting
confidence: 60%
“…buccal micronucleus by cytome assay on exfoliated buccal cells, direct/oxidative DNA damage by blood-Fpg comet assay on venous blood samples and 8-oxodGuo urinary oxidized bases by urine samples [36]. -Use of point-of-care sensors as described by Papadoupolou et al 2021 [38] (Patent no.…”
Section: Prevention-through-design In the Graphene Production Scale Upmentioning
confidence: 99%
“…The photoluminescence (PL) point for the CDs was found at 472 nm, caused by the sp 2 conjugation of the nucleus that generates a high carbonization and the reduction of functional groups with oxygen on the surface of the CDs, results coinciding with articles previously published by Papadopoulou and collaborators. 38 CD synthesized from citric acid give the CD conjugated carboxyl groups to its surface. When the CDs are conjugated with LF, the intensity of the PL decreases because of the energy transfer required for the protein to conjugate on the surface to the carboxyl groups and form an amide bond, a case that can be easily observed in Fig.…”
Section: Chemical Characterization Of CD and Cd-lfmentioning
confidence: 99%